Perancangan Sistem Informasi Perpustakaan Pada SMK Nu Hasyim Asy’ari Kab.Tegal Menggunakan PHP & MySQL - Muhamad Fatchan (Teknik Informatika, Universitas Pelita Bangsa, 2021)
Administrative activities performed by school’s library is the primary service activities in SMK NU Hasyim Asy’ari. One of the services provided by the school to the students is to provide an academic reference in the form of provision of books in the library. The students are given the opportunity to utilize a wide variety of books available in the library loan system periodically. Recording and archiving data in the library of SMK NU Hasyim Asy’ari is still using old and manual methods, it is very inefficient. To overcome this, it need a computer software that can assist and facilitate the conduct of computerization of the processes that had been done manually, so that the service can be done quickly and accurately. This library administration software built using PHP with MySQL database. The program provides options that allow to do things related to data archiving in libraries, such as the recording of members data, books, borrowing or returning books transactions and their reports. Keywords: Library,SMK NU Hasyim Asy’ari, Web-based Application, PHP, MySQL